Development of a one-step Nile blue-based imaging method to identify lipoproteins in human serum - Loe, Shelina (Nanyang Technological University, 2024)
Cardiovascular Disease (CVD) is one of the top causes of death worldwide. Clinical tests are based on estimations and calculations of Low Density Lipoprotein-Cholesterol (LDL-C) which results in misdiagnosis in certain cases. This project explores a potential Low Density Lipoprotein-Particle number (LDL-P) quantification method in human serum using a fluorescent dye. The golden fluorescence intensity exhibited by stained human serum was analysed using fluorescence spectroscopy and confocal microscopy. The concentration of LDL-P was determined using Enzyme-Linked Immunosorbent Assay (ELISA). Finally, indirect correlation between fluorescence intensity and the ELISA results was done to quantify LDL-P in human serum. The detection limits of the stained human serum were also determined with confocal microscopy and ELISA. In conclusion, the results demonstrated the potential of this dye as an indicator for LDL-P. By performing additional tests to determine the components in human serum that the dye might bind to, to ensure that the detected golden fluorescence is exclusively from LDLs, an imaging method with this dye could potentially be developed in the future. An affordable method such as this would greatly impact the healthcare industry by improving CVD diagnosis.